UPAYA SATUAN SAMAPTA MELALUI PATROLI GUNA MENCEGAH TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR DI WILAYAH HUKUM POLRES KENDAL - DECKY DANDY MURAFER DECKY MURAFER (Advances in Police Science Research Journal, 2022)
Humans in their daily life will not be separated from culture, because humans are the creators and users of culture itself. Humans live because of culture, meanwhile culture will continue to live and develop when humans want to preserve culture. The difficulty of adapting causes a lot of doubt, anxiety and conflict, both open external conflicts, and internal ones that are hidden and closed in nature. In this study, the approach used is a qualitative approach, the author describes data relating to the role of the Kendal Police Satsamapta through patrols in preventing the crime of motor vehicle theft. The results of the study found that the high number of motor vehicle theft crimes occurred because of several factors that encouraged the occurrence of motorized theft crimes, namely internal factors from the police themselves and external factors from the community. as well as from the Kasat Samapta himself, namely as a suggestion to the Kasat Samapta, namely to always supervise the activities of members, both checking the readiness of members both before the implementation and during the implementation of surveillance patrols while patrols are being carried out, namely through a live location on the WhatsApp application so that the patrol activities of members can be monitored directly.